Synergistic dual cell therapy for atherosclerosis regression: ROS-responsive Bio-liposomes co-loaded with Geniposide and Emodin - Zhenxian Li; Haimei Zhu; Hao Liu; Dayue Liu; Jianhe Liu; Yi Zhang; Zhang Qin; Yijia Xu; Yuan Peng; Lihua Ruan; Jintao Li; Yao He; et al. (Journal of Nanobiotechnology, 2024)
Abstract The development of nanomaterials for delivering natural compounds has emerged as a promising approach for atherosclerosis therapy. However, premature drug release remains a challenge. Here, we present a ROS-responsive biomimetic nanocomplex co-loaded with Geniposide (GP) and Emodin (EM) in nanoliposome particles (LP NPs) for targeted atherosclerosis therapy. The nanocomplex, hybridized with the macrophage membrane (Møm), effectively evades immune system clearance and targets atherosclerotic plaques. A modified thioketal (TK) system responds to ROS-rich plaque regions, triggering controlled drug release. In vitro, the nanocomplex inhibits endothelial cell apoptosis and macrophage lipid accumulation, restores endothelial cell function, and promotes cholesterol effluxion. In vivo, it targets ROS-rich atherosclerotic plaques, reducing plaque area ROS levels and restoring endothelial cell function, consequently promoting cholesterol outflow. Our study demonstrates that ROS-responsive biomimetic nanocomplexes co-delivering GP and EM exert a synergistic effect against endothelial cell apoptosis and lipid deposition in macrophages, offering a promising dual-cell therapy modality for atherosclerosis regression.